Evaluation of the photodegradation of Bisphenol A and Triclosan, in the presence of 6- methoxyquinoline ligand coordination compounds as singlet oxygen photosensitizers, compared to the use of the persulfate ion (2021)
ABSTRACT The importance of finding water treatment alternatives has been of great interest in the last 50 years, due to the scarcity of fresh water sources considered suitable for human consumption and the incidence of new pollutants, which each day have physicochemical characteristics. that make them difficult to remove by conventional treatments. There are some physical methodologies for the treatment of persistent organic pollutants such as adsorption, electrocoagulation and membrane filtration, however, any change in operating conditions can affect the effectiveness of the methodology, another aspect is the chemical nature of these pollutants. , high toxicity both in the analyte of interest, as well as in the reaction by-products. Advanced oxidation processes provide a very interesting alternative, which include, among others, working with active oxygen species with high oxidizing power, which has the property of carrying out reactions with organic pollutants with high effectiveness for mineralization. Within the reactive oxygen species, singlet molecular oxygen, part of the principle of the use of a photosensitizing material capable of being activated with light, promoting an energy gain for the activation of oxygen in the triplet state and passing it to the singlet state, with it generated leading to the degradation of pollutants in low concentrations in very short times, reaching mineralization. In this doctoral thesis, the photodegradation of bisphenol A and triclosan was evaluated using a 6-methoxyquinoline ligand coordination compound with singlet molecular oxygen photosensitizing activity. To achieve this objective, two compounds were synthesized as photosensitizers using the ligand 6-methoxyquinoline, gold (Au) and manganese (Mn) were used as precursors, thermogravimetric analysis (TGA) and differential scanning calorimetry analysis (DSC) demonstrated that only one of them had thermostable characteristics and that in the case of the manganese complex the formation of the association complex, verified by the Benesi-Hildebrand analysis and the TGA-DSC analysis. The morphological characterization was carried out by transmission electron microscopy (STEM), RAMAN and FITR-ATR Infrared spectroscopy analysis demonstrated the formation of the new complexes, as well. According to the experimental design, a screening analysis was carried out for both the standard photosensitizer and the synthesized complex, it was possible to establish that there is a degradation pathway by singlet molecular oxygen, in addition photodegradations that oscillate for Bisphenol A by 20% and for triclosan by 50%, with a tendency to acid pH. In the case of degradation products, it was possible to establish some of the degradation products such as 4-isopropenylphenol for Bisphenol A, in the case of triclosan, quinoline derivatives were created as a result of its transformation. Regarding the comparison with the persulfate chemical method, the results were not comparable since this species is promoted at basic pHs and also the conditions in which this research was carried out were not detectable, since the reaction occurred too fast.